Pemberian Edukasi Kesehatan pada Orang Tua Mengenai Pencegahan Kekerasan Seksual pada Anak Usia Pra Sekolah di TK PUI II Sindang: Providing Health Education to Parents Regarding Prevention of Sexual Violence in Preschool Age Children at TK PUI II Sindang - Sholihah, Amalia Rizqi; Irmawati, Novi Dwi; Hardivianty, Cynthia; Purbasary, Eleni Kenanga (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Sexual violence is one of the problems that most often occurs in children. Children who have been victims of sexual violence will experience several negative impacts such as emotions, depression, loss of appetite, introversion, insomnia, and inability to focus at school. This community service activity aims to increase parents' knowledge about preventing sexual violence in pre-school children. The method used is lecture and question and answer. Activity procedures include a pre-test, providing material on preventing sexual violence against children, discussion, giving leaflets and post-test. The targets of this community service activity were parents whose children attended TK PUI II Sindang with a total of 23 respondents. Before the counseling was given, more than half (52.2%) of the participants already had good knowledge and after the counseling was given the parents' knowledge increased (100%). There is an increase in knowledge among parents after being given health education. Community service activities need to be carried out on an ongoing basis so that acts of sexual violence against children do not occur.